The Role of Ancient Fishing on the Desert Coast of Patagonia, Argentina - Scartascini, Federico Luis (2017)
This article explores latitudinal and chronological variations in the exploitation of marine fish by the hunter-gatherers who occupied the Atlantic coast of continental Patagonia, Argentina, since the mid-Holocene. Results indicate a spatial gradient in the importance of fish. A significant reduction in the frequency of fish remains in the archaeological sites occurs at higher latitudes. The chronological trends identified also suggest differences between the assemblages of the northern and southern coasts of this long littoral area. The results obtained are further discussed in relation to identified environmental and cultural variation.